Common Metals as Electrodes for Leak‐Free Organic Light‐Emitting Devices Using Extraordinary Thick Phosphotungstic Acid Buffer Layers. Issue 23 (6th September 2022) - Ohisa, Satoru; Oono, Taku; Miyakawa, Masashi; Shimizu, Takahisa; Tsuzuki, Toshimitsu
Abstract: Electrical leakage is one of the fatal faults associated with thin‐film devices (TFDs) including organic light‐emitting devices (OLEDs). To prevent electrical leakage, highly smooth electrodes are required to avoid the concentration of the electric field at local points. However, this requires the use of expensive electrode substrates. Here, OLEDs using inexpensive, aluminum‐foil‐based electrode substrates with an extremely high surface roughness are fabricated. A low leakage current is realized by incorporating extraordinary thick buffer layers of phosphotungstic acid (PWA) exhibiting the negative differential resistance (NDR) property. In its pristine state, PWA exhibits a high electrical resistance. However, upon applying electric current, the resistance is significantly decreased, resulting in increased conductivity and expression of NDR property, owing to the formation of conductive filaments and charge‐storage effects. The OLEDs produced with PWA achieve a low‐driving voltage and high external quantum efficiency simultaneously. Aluminum‐foil‐based OLEDs with a light‐emission area of 64 cm 2 are fabricated. They emit steady luminescence even in crumpled and torn states. To the best of authors' knowledge, this is the first report of a large‐area OLED exhibiting steady luminescence in such deformed states. Abstract : Organic light‐emitting devices (OLEDs) using inexpensive, aluminum‐foil‐based electrode substrates with an extremely high surface roughness are fabricated. A low leakage current is realized by incorporating extraordinary thick buffer layers of phosphotungstic acid exhibiting the negative differential resistance property. The OLEDs with a light‐emission area of 64 cm 2 emit steady luminescence even in crumpled and torn states.